Effects of enterprise carbon trading mechanism design on willingness to participate——Evidence from China - Zha, Dao-Shun; Feng, Tian-Tian; Kong, Jia-Jie (Frontiers in Environmental Science, 2022)
At this stage, the air pollution problem represented by climate warming has become very serious, and it is important to establish a carbon emission trading system as an innovative policy tool to promote energy savings and emission reduction. China's carbon trading market is currently in its initial stage, and only power generation enterprises are included in the market. When faced with changes in the carbon trading market mechanism, enterprises are often unable to make rapid adjustments, making it difficult to reflect the carbon market's role in reducing emissions. Current research on the design of carbon trading mechanisms of enterprises has lacked investigation into the influence of the design of carbon trading mechanisms on the willingness of enterprises to participate from the perspective of enterprises. In this paper, we use choice experiments, a conditional logit model and a multinomial logit model to explore the impacts of changes in the design of enterprise carbon trading mechanisms on enterprise willingness to participate in carbon trading. The impacts of all attributes on the willingness to participate in national carbon trading is ranked from largest to smallest: offset mechanism > carbon product trading > government penalty > carbon quota allocation. Based on the research results, relevant policy recommendations and corporate countermeasures are proposed to improve corporate willingness to participate in carbon trading and encourage active cooperation in energy saving and emission reduction activities.